Correction: Naphthalene flanked diketopyrrolopyrrole based organic semiconductors for high performance organic field effect transistors. (5th September 2018) - Liu, Qian; Sun, Huabin; Blaikie, Chula; Caporale, Chiara; Manzhos, Sergei; Feron, Krishna; MacLeod, Jennifer M.; Massi, Massimiliano; Bottle, Steven E.; Bell, John; Noh, Yong-Young; Sonar, Prashant
Abstract : Correction for 'Naphthalene flanked diketopyrrolopyrrole based organic semiconductors for high performance organic field effect transistors' by Qian Liu et al., New J. Chem., 2018, 42, 12374–12385.